2020
DOI: 10.1093/nar/gkaa263
|View full text |Cite
|
Sign up to set email alerts
|

O-GlcNAc regulates gene expression by controlling detained intron splicing

Abstract: Intron detention in precursor RNAs serves to regulate expression of a substantial fraction of genes in eukaryotic genomes. How detained intron (DI) splicing is controlled is poorly understood. Here, we show that a ubiquitous post-translational modification called O-GlcNAc, which is thought to integrate signaling pathways as nutrient conditions fluctuate, controls detained intron splicing. Using specific inhibitors of the enzyme that installs O-GlcNAc (O-GlcNAc transferase, or OGT) and the enzyme that removes O… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 80 publications
5
79
0
Order By: Relevance
“…By quantifying how much each OGT activity impacts the abundance of each protein in the cell, we have identified the biological pathways most affected by each OGT activity. Consistent with known roles for O-GlcNAc, we found that Ser/Thr glycosylation broadly regulates metabolism and gene expression, with enriched pathways including splicing (44), translation (69)(70)(71), and autophagy (72)(73)(74). Among the pathways linked to OGT's noncatalytic activities are oxidative phosphorylation, the electron transport chain, and components of the actin cytoskeleton, consistent with prior data suggesting OGT binds to the actin-regulating Ecadherin/beta-catenin complex (39).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…By quantifying how much each OGT activity impacts the abundance of each protein in the cell, we have identified the biological pathways most affected by each OGT activity. Consistent with known roles for O-GlcNAc, we found that Ser/Thr glycosylation broadly regulates metabolism and gene expression, with enriched pathways including splicing (44), translation (69)(70)(71), and autophagy (72)(73)(74). Among the pathways linked to OGT's noncatalytic activities are oxidative phosphorylation, the electron transport chain, and components of the actin cytoskeleton, consistent with prior data suggesting OGT binds to the actin-regulating Ecadherin/beta-catenin complex (39).…”
Section: Discussionsupporting
confidence: 86%
“…Expected outliers in the data further validated the regression analysis ( Figure 4E). For example, OGA abundance is known to decrease with low protein O-GlcNAc levels (40,44), and we found that OGA had the most negative β GlcNAc value after two days of dTAG-13 treatment.…”
Section: Simultaneous Comparison Of Multiple Cell Lines Quantifies Efmentioning
confidence: 64%
See 2 more Smart Citations
“…While we were getting our revised manuscript ready for submission, evidence was reported for similar function of O-GlcNAc in intron splicing in metazoan and for broad presence of stress-dependent intron retention in plants. Interestingly, inhibition of OGT was found to increase splicing of detained introns in human cells 61 . Detained introns are a novel class of post-transcriptionally spliced (pts) introns, which are one or few introns retained in transcripts where other introns are fully spliced 62 .…”
Section: Discussionmentioning
confidence: 99%